Leadership and Its Impact on Organisational Behaviour in a Nuclear Power Plant (NPP) - Al Ali, Bader (2019)
This study seeks to critically investigate the impact that various leadership style have on organisational behaviours that are crucial in maintaining high organisational performance with respect to an NPP in the UAE. The leadership styles under consideration include transformational leadership, transactional leadership and LMX. The study identified a number of independent, dependent, and sub-variables to address the research questions and objectives. A comprehensive analysis of the existing literature was carried out and the variables like job satisfaction, job performance, professional development, and employee motivation was identified. The research is based on quantitative research approach to test the relationship between leadership style and different sub-variables. The data was gathered through a questionnaire that had closed-ended questions based on 5-point Likert Scale. The questionnaire along with the introductory letter was sent to employees under the different management categories at the NPP. Various statistical tests were carried out to establish the relationship between variables. The study found that transformational and LMX leadership styles have a significant impact on job satisfaction while the impact of transactional leadership style is significantly negative. One-way ANOVA was carried out to analyse the difference between the sub-dependent variables that revealed significant difference in job satisfaction among different management groups.